DISKURSUS PERLINDUNGAN HUKUM BAGI TENAGA KERJA INDONESIA DALAM PENEMPATAN DI MALAYSIA - Adnan Hamid (Arena Hukum, 2019)
AbstractThe increase in the number of Indonesian workers who work abroad to become migrant workers, among others, is driven by economic problems and / or the difficulty of getting employment in the country, while at the same time the demands of life must be fulfilled. The purpose of this article is to analyze the policies taken by the government in the placement and protection of Indonesian workers who work abroad as migrant workers. In this article, the author conducts a normative juridical study with a study of various Acts and regulations that apply specifically to Indonesian workers who work in Malaysia. From the results of the study, it shows that Indonesian workers who works as migrant workers are in Malaysia and most of those migrant workers are officially undocumented or known to be illegal migrant workers and thus have an impact on the protection of migrant workers themselves. Based on the foregoing, the author concludes that the government must strive to provide protection to Indonesian workers who work as migrant workers by, among other things, carrying out various revisions to Acts and regulations and must be pro-active in carrying out the bilateral agreement with the receiving country.Â AbstrakPeningkatan jumlah TKI yang bekerja di luar negeri untuk menjadi pekerja migran, antara lain didorong oleh permasalahan ekonomi dan/atau sulitnya mendapatkan lapangan pekerjaan di dalam negeri, sementara pada saat yang sama tuntutan hidup harus tetap terpenuhi. Tujuan dalam penulisan artikel ini adalah untuk menganalisis kebijakan yang diambil oleh pemerintah dalam penempatan dan perlindungan bagi tenaga kerja Indonesia yang bekerja di luar negeri sebagai pekerja migran. Di dalam penulisan ini, penulis melakukan penelitian secara yuridis normatif dengan kajian terhadap berbagai peraturan perundang-undangan yang berlaku khususnya terhadap tenaga kerja Indonesia yang bekerja di Malaysia. Dari hasil penelitian, menunjukkan tenaga kerja Indonesia yang bekerja sebagai pekerja migran terbanyak berada di negara Malaysia dan sebagian besar pekerja migran tersebut adalah tidak berdokumen resmi atau dikenal dengan pekerja migran ilegal sehingga berdampak pada perlindungan bagi pekerja migran itu sendiri. Berdasarkan hal tersebut di atas, penulis berkesimpulan agar pemerintah harus berupaya dalam memberikan perlindungan kepada tenaga kerja Indonesia yang bekerja sebagai pekerja migran dengan antara lain melakukan berbagai revisi peraturan perundang-undangan dan harus pro aktif dalam melakukan perjanjian bilatera dengan negara penerima.